2019
DOI: 10.18203/2320-1770.ijrcog20192458
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of vulvar lesions: patient’s anxiety, clinician’s concern and pathologist’s diagnostic challenge

Abstract: Background: A wide variety of inflammatory, premalignant and malignant lesions can occur on the vulva. Some of the lesions are limited to the vulva, while some also involve other parts of the body. Although vulvar diseases can cause a significant issue in the patients, they are less commonly discussed than those of cervix, uterus and ovary. Most of the asymptomatic lesions remain un-noticed, and are seen during routine gynecological checkups. Common complaints in symptomatic lesions are lumps, discomfort, itch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
2
1
Order By: Relevance
“…in 3rd decade as seen in other studies. 3 Most of the patients (38 to 46%) in other studies 4,5 were postmenopausal while in our study only 10.26% patients were post-menopausal.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…in 3rd decade as seen in other studies. 3 Most of the patients (38 to 46%) in other studies 4,5 were postmenopausal while in our study only 10.26% patients were post-menopausal.…”
Section: Discussioncontrasting
confidence: 50%
“…In our study we found two cases of Hidradenoma papilliferum accounting for 5.13% of total cases. Reported incidence of Hidradenoma papilliferum in other studies 3,4 ranges from 1,3% to 8.82%.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation